DINAMIKA PENELITIAN KEPATUHAN WAJIB PAJAK - Sri Ayemi; Yhoga Heru Pratama; Jauzaa Azahroo Oksidea Oksidea; Fransiskus Vilisianus Sales (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study explores the compliance of taxpayers in Indonesia from 2013 to 2023 by mapping research published in national scientific journals. The research methodology involves a thorough literature review, examining articles with the keyword "taxpayer compliance" on scientific journal websites. The population consists of articles on taxpayer compliance, and the sample is selected based on criteria such as keyword relevance, completeness, clarity, and online accessibilityThe mapping of journal names aims to categorize articles, facilitating information on journal consistency in publishing content related to taxpayer compliance. The findings reveal continuous publications on taxpayer compliance in scientific journals throughout the years, with 2017 dominating the articles. E-Jurnal Akuntansi emerges as the most prolific journal in publishing these articles. The prevalent research method is quantitative, with awareness of taxpayers being the most commonly studied variable. Implications of the study include recognizing E-Jurnal Akuntansi and Jurnal Akuntansi as promising channels for future researchers and the potential for more varied and in-depth results through the use of qualitative methods. The study also highlights the predominance of primary data sources and suggests the exploration of alternative sources such as observation and interviews for richer and more realistic data.